The alliance between China and Russia and the rivalry between China and the USA in light of the war in Ukraine - Xing, Li (Politica, 2023)
This article aims to explain and analyze the complexity of the Ukraine War by scrutinizing two important factors – the China-Russia alliance and the China-US rivalry. The article demonstrates that these two factors and their interconnections largely determine the nature and trend of the developing world order. Beijing’s position on the Ukraine War reflects its strategic calculations through the lens of great power rivalry between itself and Washington. The China-Russia alliance is a utility, and the Ukraine War is a good situation for Beijing and Russia to promote a new international security architecture that is not dominated by the West. The article concludes that Russia’s war in Ukraine combined with the China-US rivalry and decoupling is propelling the return of conventional geopolitical competition and division. The fact that the world is divided over these events shows that we may be heading towards a multi-order world.